2021
DOI: 10.1186/s12889-020-10071-2
|View full text |Cite
|
Sign up to set email alerts
|

Less than one-fifth of the mothers practised exclusive breastfeeding in the emerging regions of Ethiopia: a multilevel analysis of the 2016 Ethiopian demographic and health survey

Abstract: Background The burden of low coverage of exclusive breastfeeding (EBF) has a significant impact on the health of a newborn and also on the family and social economy in the long term. Even though the prevalence of EBF practices in Ethiopia is low, the practices in the pastoral communities, in particular, are significantly low and affected by individual and community-level factors. Besides, its adverse outcomes are mostly unrecognised. Therefore, this study aimed to assess the individual and comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…Regarding the sample size of the included studies, it ranged from 119 [ 28 ] to 1769 [ 32 ] in which both these studies were from Amhara region. The prevalence of EBF practice among the individual studies also ranged from 17.28% [ 37 ] to 88.19% [ 38 ]. Regarding quality scores of the studies, the JBI checklist of critical appraisal of observational studies was used.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the sample size of the included studies, it ranged from 119 [ 28 ] to 1769 [ 32 ] in which both these studies were from Amhara region. The prevalence of EBF practice among the individual studies also ranged from 17.28% [ 37 ] to 88.19% [ 38 ]. Regarding quality scores of the studies, the JBI checklist of critical appraisal of observational studies was used.…”
Section: Resultsmentioning
confidence: 99%
“…The association between employment statuses of women with EBF practice of women was assessed by computing the pooled odds ratio. A total of 24 articles were eligible to estimate the POR [ 8 , 9 , 20 – 22 , 24 , 28 – 30 , 33 35 , 37 , 38 , 48 51 , 53 55 , 57 59 ]. Thus, employment status of women was significantly associated with the EBF practice of women in Ethiopia.…”
Section: Resultsmentioning
confidence: 99%
“…Scientifically other studies have also argued that the relationship between diarrhea and EBF is due to the protein lactoferrin, which is found in breast milk in all age groups. Thus in lymphocyte growth factors, lactoferrin can destroy disease-causing pathogens to reduce the inflammatory response and can increase the activity of the immune system [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…9 Maternal-level factors, such as the desire for more children and lower household socioeconomic status, were associated with a decreased likelihood of practicing EBF. 9 In another study that also relied on Ethiopian DHS data, maternal demographic variables such as education level, maternal age, region, religion, and socioeconomic status were associated with breastfeeding status. 10 While both studies used DHS data, many of their analyses were conducted using different variables.…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted in Debre Markos, Ethiopia showed that mothers' breastfeeding knowledge and education during their antenatal/postnatal care visits and mothers' unemployment status were significantly and positively associated with EBF 1 . A study using 2016 Ethiopian Demographic and Health Survey (DHS) data showed that less than 20% of women in Ethiopia practiced EBF in Afar, Gambella, Somali, and Beninshangul, the “Emerging regions” of the country, which are characterised as having relatively low socioeconomic status, among other factors 9 . Maternal‐level factors, such as the desire for more children and lower household socioeconomic status, were associated with a decreased likelihood of practicing EBF 9 .…”
Section: Introductionmentioning
confidence: 99%